Green zero-valent iron nanoparticles for the degradation of amoxicillin - Machado, S. (2019)
In the last years, it has been proven that zerovalent iron nanoparticles, including those produced using green methods, are efficient remediation agents for a wide range of target contaminants. However, apart from the known advantages of these green nanomaterials, the knowledge of how they act on distinct contaminants is not yet fully understood and requires further investigation. The objectives of this work were to study the degradation of a common antibiotic, amoxicillin, in water and in a sandy soil using green zero-valent iron nanoparticles (gnZVIs) as reductants and as catalysts for the Fenton reaction. It represents the first study of the use of gnZVI, as alternative for the zero-valent iron nanoparticles produced with sodium borohydride, for the degradation of amoxicillin. The results of the performed tests indicate that gnZVIs have the potential to be used in remediation processes. In both chemical tests, the gnZVI was able to degrade up to 100% of amoxicillin in aqueous solutions, using an amoxicillin/ gnZVI molar ratio of 1:15 when applied as a reductant, and an amoxicillin/H2O2/gnZVI molar ratio of 1:13:1 when applied as a catalyst for the Fenton reaction. The soil tests showed that the required molar ratios for near complete degradation were higher in the reduction test (1:150) than in the gnZVI-catalyzed Fenton reaction (1:1290:73). This is possibly due to parallel reactions with the soil matrix and/or limitations of the reagents to reach the entire soil sample. The degradation efficiencies obtained in these tests were 55 and 97% for the reduction and catalyzed Fenton processes, respectively.